Utilization of mobile phones for accessing menstrual regulation services among low-income women in Bangladesh: a qualitative analysis - Messinger, Chelsea Jordan; Mahmud, Ilias; Kanan, Sushama; Jahangir, Yamin Tauseef; Sarker, Malabika; Rashid, Sabina Faiz (© 2017 BioMed Central Ltd., 2018)
This article was published in the Reproductive Health [© 2017 The Author(s).] and the definitive version is available at: http://doi.org/110.1186/s12978-016-0274-1 The Journal's website is at: https://www.ncbi.nlm.nih.gov/pubmed/28088232